SIMBOL KEAGAMAAN DALAM ISLAM DAN IDEOLOGI TELEVISI - Solikhati, Siti (Islamic Communication Journal, 2017)
Basically human lives are built based on fragmented symbols which form the real picture of the whole world. People expressed every side of their lives (including religious live) using certain symbols which are socially accepted. The discussion on religious symbols has always leads to two means, namely socio-cultural symbols which associate religious doctrines with the local culture, and normative symbols which are supposed to be permanent symbols. The discussion on this paper focused on the nuance of the meaning of religious symbols which have shifted more on cultural meaning rather than the normative ones, as can be seen on television religious programs.Accordingly, television has its own way of expressing things based on their own management policy, in which usually they use market needs as the main reason. To fulfill the market needs however, the medium need to wrap religious message up using certain symbols to fit their audience needs. According to Fiske (1987) it will be easier to have a look the ideology used by television by take a close look at how it uses certain symbols.---------------------------------------------------------------------------------------Kehidupan manusia ini terdiri dari serpihan-serpihan simbol yang kemudian terpola dan membentuk kesatuan dunia secara utuh. Manusia mengekspresikan diri, termasuk di    dalamnya    mengekspresikan    aspek    kehidupan    beragama menggunakan simbol yang telah disepakati secara sosial. Wacana simbol dalam kehidupan beragama  mengandung  makna  multi dimensi,  yaitu  dimensi  sosiokultural  yang  bisa berubah  sesuai  dengan  konteks, serta dimensi  normative  yang  bersifat  permanen  dan mutlak. Konteks wacana symbol keagamaan dalam paper ini difokuskan pada pergeseran makna symbol keagamaan yang bersifat normative lebih banyak berfungsi sebagai symbol kultural sebagaimana diperlihatkan pada tayangan-tayangan keagamaan di televisi. Televisi memiliki cara tersendiri untuk mengemas informasi tertentu berdasarkan konsep kebijakan internal dan menggunakan argument segmen audience. Untuk memenuhi target audience, maka televisi perlu mengemas pesan keagamaan menggunakan symbol yang telah disesuaikan dengan kebutuhan audience. Menurut Fiske (1987) dengan melihat bagaimana televisi menggunakan symbol-simbol tertentu, maka akan mudah untuk melihat ideologi yang terkandung di dalamnya.